Historical Analysis of Educational Legislations for the Formal Education of the Negros in Brazil - BETTINE, MARCO; SANCHEZ, LIVIA PIZAURO (Faculdade de Filosofia e Ciências, 2017)
This article is the result of seeking to investigate and understand the process of implementation of educational laws that act on black and black lives in the formal education process. Outlines this is the gap between the proclaimed and planned and reality. Thus, we understand that the laws studied here represent a movement of tension towards democratization of the curriculum and the school itself, because it allows less visible populations and valued in this institution and in their social practices are recognized in their stories, take voice, actively participate constant construction and reconstruction of school routine. Recebido em: 06/10/2016.Aprovado em: 24/02/2017.